Effects of training and detraining on muscle strength in rowers - Janjic, N.; Maricic, M.; Zubnar, A.; Karan, V.; Drapšin, M.; Klašnja, A. (Medicinski pregled, 2019)
Introduction. Annual and periodized training protocols significantly affectthe muscle adaptation in rowers. Considering that the main goal of the training period is increasing specific muscle strength and of detraining period increasing general strength and active rest, the aim of this study was to compare the strength of different muscle groups between training and detraining periods. Material and Methods. The study was conducted at theDepartment of Physiology, Faculty of Medicine Novi Sad, and it included 34male and female rowers, 15 to 18 years of age. The muscle strength was measured using a Concept 2 DYNO dynamometer. The strength of the arm extensors and flexors, as well as the leg extensors was measured twice, at the end of the competition season (peak of performance) and before the beginning of the preparation season (after detraining). Results. A statistically significant decrease was found in absolute and relative muscle strength, flexor and arm extensor contraction rate, as well as relative leg extensor strength and contraction rate during the training and detraining periods (p 0.05). Conclusion. Periodization ofthe annual training program in rowers has a higher impact on differences inthe upper limb muscle adaptation, compared to lower limb muscles in terms of absolute strength.